(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2015)
The Magnetic Barkhausen noise (MBN) technique measures discrete changes in magnetization, known as “Barkhausen jumps”, whi ch can be seen as steps i n the hysteresis curve. When a ferro-magnetic material is subjected to an external varying magnetic field, the magnetization of the material wil l change in a non-linear way. These changes in magnetization are described by the hysteresis curve and are the result of modifications of domain structure of the material. Changes in magnetization are caused by domain wall creation, domain wall annihilation, domain wall motion and rotation. In order to improve the interpretation of Barkhausen noise, models are needed which describe the dependence of magnetization on material properties.